Freestyle gymnastic exercise can be used to assess complex coordination in a variety of sports - Olajos, A. A.; Takeda, M.; Dobay, B.; Radak, Z.; Koltai, E. (Journal of Exercise Science & Fitness, 2020)
Objective: The assessment of motor coordination is a very complex process and demonstrates a high degree of sport specificity. There are a limited number of tests, if any, where results correlate with the success rate of athletes in different sports. Methods: Free style gymnastic exercise (FSGE) and coordination ball dribbling exercise (CBDE) were used to see whether the execution quality of these tests is related to the quality of athletes from team handball, water polo, kayak, rhythmical gymnastics (RG) and aerobics (222 athletes - 75 male, 147 female; 23 non-athletes - 9 male, 14 female). Results: FSGE results related to the quality of performance in all sports (r = -0.232, p < 0.01 in handball, water polo, kayak and r = -0.26, p < 0.05 in aerobics and RG), while CBDE did not. Older players had higher ranking as they had more time to be successful at their sport (r = -0.498, p < 0.01 in handball, water polo, kayak; r = -0.298, p < 0.05 in aerobics and RG). The scores of FSGE were independent from the age and gender of the subjects. Conclusions: The main findings were: (i) that athletes did significantly better than the controls in both tests; (ii) RG and aerobics athletes did better on the FSGE than handball, water polo players and kayakers; (iii) handball players did better than kayakers, RG and aerobics athletes on the CBDE test; and (iv) better ranked athletes performed better on the FGSE test. Therefore, FSGE test appears to be a reliable test to assess coordination in variety of sport and different levels of sport performance.